2002
DOI: 10.1002/em.10110
|View full text |Cite
|
Sign up to set email alerts
|

Malsegregation as a possible mechanism of aneuploidy induction by metal salts in MRC‐5 human cells

Abstract: Many aneugenic compounds are known to affect one or more components of the mitotic apparatus leading to an erroneous migration of chromosomes. Malsegregation occurs when a chromosome (or a chromatid) fails to migrate and remains at the metaphase plate. Nondisjunction implies the lack of dissociation between sister chromatids and the migration of both together to the same pole. The aim of the present study was to provide evidence that the aneugenic effect of some metal salts is the consequence of malsegregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Ochi et al showed that both organic and inorganic arsenic can induce aneuploidy after only 48 hours of exposures in Syrian hamster embryo cells. Another study in normal human lung fibroblasts showed that a 30-hour exposure to cadmium chloride, potassium dichromate, or dimethylarsinic acid had an aneugenic effect (31). Therefore, these data suggest that aneuploidy is an early step in the development of cancer.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Ochi et al showed that both organic and inorganic arsenic can induce aneuploidy after only 48 hours of exposures in Syrian hamster embryo cells. Another study in normal human lung fibroblasts showed that a 30-hour exposure to cadmium chloride, potassium dichromate, or dimethylarsinic acid had an aneugenic effect (31). Therefore, these data suggest that aneuploidy is an early step in the development of cancer.…”
Section: Discussionmentioning
confidence: 87%
“…Once inside the cell, the Cr ions induce the cytotoxic, growth-inhibiting, and genotoxic effects observed after exposure to lead chromate and the lead ions have no apparent effect (14,15,17,18). Thus far, the potential effects of Cr ions on centrosome amplification have not been studied, but a 30-hour exposure to soluble chromate induced aneuploidy, which suggests that Cr ions could have the capacity to cause centrosome amplification, although that study did not consider it (31). On the other hand, it is possible that lead ions could contribute to lead chromate-induced centrosome amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules are the prime components involved in chromosomal segregation, their functional accuracy ensuring maintenance of the normal karyotype in the progeny. Schistosoma haematobium-induced disruption of microtubules during mitosis can lead to aneuploidy (Voutsinas et al 1997;Seoane et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that Cd and Pb can cause chromosomal lesions by altering the reduction-oxidation state within cells, thus releasing free radicals that can damage the structure of DNA (Hartwig et al 2002;Lin et al 2005). Cadmium also may interfere with the mitotic apparatus and cause aneuploidy in exposed cells (Gü erci et al 2000;Seoane and Dulout 2001;Seoane et al 2002), and Zn can induce chromosome gaps and breaks in vivo (Hikiba et al 2005).…”
Section: Introductionmentioning
confidence: 97%